Difference in volatile profile between pericarp tissue and locular gel in tomato fruit - Li-bin WANG; Jinhe Bai; Zhi-fang YU (Journal of Integrative Agriculture, 2016)
Aroma, a complex mixture of volatile compounds, plays an important role in the perception and acceptability of tomato products by consumers. Numerous studies have reported volatile profiles in tomatoes based on measurement of the whole fruit or pericarp tissue, however, little is understood regarding the volatile compositions in the inner tissues. The objective of this study was to investigate the differences in volatile profile between pericarp tissue and locular gel in tomato fruit. Based on HS-SPME-GC-MS analysis, totally 42 volatile compounds were detected in FL 47 and Tasti-Lee tomato fruits. Regardless of cultivars, a substantial higher concentration of total volatile compounds was observed in pericarp than that in locular gel, associated with higher levels of aldehydes, hydrocarbons, and nitrogen compounds. Pericarp tissue possessed higher levels of cis-3-hexenal, hexanal, heptanal, octanal, nonanal, cymene, terpinolene, undecane, dodecane, 2-phenylethanol, 6-methyl-5-hepten-2-one, 2-methylbutyl acetate, 1-nitro-pentane, and 1-nitro-2-phenylethane, while the abundances of 2-methylpropanal, butanal, 2-methylbutanal, 2-methyl-2-butenal, 2-methylpropanol, 3-methylbutanol, 2-methylbutanol, and 2-butanone were higher in locular gel. Principal component analysis (PCA) and cluster analysis using GC-MS and electronic nose (E-nose) data discriminated the two tissues.